2018
DOI: 10.1016/j.jimonfin.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

International spillovers of monetary policy: Evidence from France and Italy

Abstract: In this paper we provide empirical evidence on the impact of US and UK monetary policy changes on credit supply of banks operating in Italy and France over the period 2000-2015, exploring the existence of an international bank lending channel. Exploiting bank balance sheet heterogeneity, we find that monetary policy tightening abroad leads to a reduction of credit supply at home, in particular for US monetary policy changes. Our results show that USD funding plays an important role in the transmission mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Gajewski et al (2019) document the importance of bank lending in the transmission of foreign monetary policies for Chile, Korea, and Poland. The international bank lending channel has also been confirmed for Italy and France in Schmidt et al (2018). Argimon et al.…”
Section: Introductionmentioning
confidence: 74%
“…Gajewski et al (2019) document the importance of bank lending in the transmission of foreign monetary policies for Chile, Korea, and Poland. The international bank lending channel has also been confirmed for Italy and France in Schmidt et al (2018). Argimon et al.…”
Section: Introductionmentioning
confidence: 74%
“…For instance, Curcuru and Kamin (2018) find that conventional Fed policies exert greater international spill-overs than unconventional policies (such as QE), Albagli et al (2018) show that US monetary policy spill-overs to long-term yields have increased substantially after the global financial crisis, while Yang and Zhou (2017) report a significant contribution of Fed unconventional policy to international volatility spill-overs. In addition, Schmidt et al (2018) provide evidence on the impact of US and UK monetary policy shocks on domestic credit supply of French and Italian banks; Georgiadis (2015) documents that US monetary policy generates sizable output spill-overs to the rest of the world; Hanisch (2018) shows that US monetary policy has a substantial impact on individual EA economic and financial stability, with financial sector represented by bond, stock and credit markets serving as an active transmission channel. In order to detect potential US monetary policy spill-over effects, we employ the same FAVAR model as above for the Eurozone sample markets, except that instead of using ECB policy we use Fed standard (FFR) and nonstandard (y*) monetary policy.…”
Section: Spill-over Effectsmentioning
confidence: 99%
“…Previous studies on risk transmission mechanisms also showed that some monetary policies transmitted risks by expanding assets and deposits or stimulating aggregate demands through wealth channels. Another interesting perspective that has been explored by previous studies is the response of monetary and financial services companies to contrasts between monetary policy and regulatory expectations, and that the specific risk transmission is dependent on the heterogeneity across assets and liabilities, market concentration, enterprise size, liquidity, and leverage ratio [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%